Specification for textile reinforced thermoplastics hydraulic hoses and hose assemblies (BSI, 1992)
Flexible pipes, Pipes, Thermoplastic polymers, Plastics, Reinforced materials, Textile fibres, Hydraulic equipment, Service pressure, Temperature, Dimensions, Test pressure, Bending, Radius, Performance, Leak tests, Testing conditions, Marking, Electrical conductivity, Electrical testing